L'équilibre de la relation entre investisseur étranger et État hôte dans la jurisprudence arbitrale - Jorland, Maxime (Université Paris-Saclay, 2025)
Le droit des investissements internationaux s'est construit sous l'impulsion des tribunaux arbitraux qui, dans leur rôle d'interprétation du droit international coutumier et des traités d'investissement, ont contribué à enrichir le droit matériel des investissements. La multiplication des sentences rendues a constitué progressivement une véritable jurisprudence, visant à équilibrer la relation entre l'investisseur étranger et l'État hôte. Cependant, l'interprétation des traités par les tribunaux arbitraux s'est souvent faite dans un objectif de protection de l'investisseur face à la puissance publique de l'État, jusqu'à inverser parfois le rapport de force entre les deux opérateurs. De plus, l'absence de principe de précédent en arbitrage d'investissement a contribué à créer un flou notionnel, du fait des interprétations changeantes des dispositions des traités protégeant l'investisseur étranger. 2Cette étude vise donc à faire état du droit positif des investissements internationaux en déterminant un courant doctrinal commun aux sentences arbitrales. Une fois ce travail de compilation réalisé, l'objectif sera alors de déterminer l'état de l'équilibre des forces entre les deux opérateurs et proposer un rééquilibrage du droit des investissements. Ce rééquilibrage passe notamment par une redéfinition des critères jurisprudentiels imprécis ou changeants et une adaptation de la protection de l'investisseur étranger aux enjeux modernes du commerce international, tout en veillant à permettre à l'Etat hôte de conserver ses prérogatives de puissance publique. International investment law has largely been shaped by arbitral tribunals, whose interpretative function with regard to customary international law and investment treaties has contributed significantly to the development of substantive investment law. The proliferation of arbitral awards has progressively given rise to a de facto jurisprudence, aimed at striking a balance between the interests of foreign investors and the sovereign rights of host States. However, treaty interpretation by arbitral tribunals has often been guided by a protective logic in favour of the investor, at times to the extent of inverting the power dynamic between the two actors. Furthermore, the absence of a binding precedent doctrine in investment arbitration has fostered conceptual uncertainty, resulting from fluctuating interpretations of the treaty provisions safeguarding foreign investors.This study seeks to provide an overview of the current state of positive international investment law by identifying a coherent doctrinal trend emerging from arbitral case law. Based on this synthesis, the aim is to evaluate the prevailing balance of power between the investor and the host State, and to propose avenues for rebalancing investment law. Such rebalancing entails, in particular, a clarification of vague or inconsistent jurisprudential standards and an adaptation of investor protection to contemporary challenges of international trade, while ensuring that host States retain their sovereign regulatory authority.
Keywords: Arbitrage; Arbitrage commercial international; Arbitration; CIRDI; Etat hôte; FDI; Host state; ICSID; International; Investissements; Investissements étrangers; Investisseur; Investments; Investor

Analyse critique du développement de la médiation en France : les résistances à l'essor de la médiation en droit privé - Prêté, Safya Bayoub (Université Bourgogne Franche-Comté, 2025)
La médiation est une technique de communication faisant intervenir un tiers impartial, neutre et indépendant, pour aider des individus à trouver une issue à leur crise conflictuelle. Par essence, la médiation est un outil de résolution des conflits pacifiant, fondé sur la responsabilisation des parties. Attrayante par sa souplesse, louée pour son coût présenté comme modéré, le législateur en a encouragé l’expansion. Alors que l’article 21 du code de procédure civile confie au juge la mission de concilier les parties, la médiation devient l’un des outils privilégiés par les pouvoirs publics pour permettre la réalisation de cette mission. Ainsi, la loi n°95-125 du 8 février 1995, relative à l’organisation des juridictions et à la procédure civile, pénale et administrative, institue la médiation judiciaire. Elle marque le début d’un ancrage législatif en faveur de ce processus. Ce premier mouvement en faveur de la médiation s’est accéléré en France, à l’initiative de l’Union européenne qui a fait adopter le 21 mai 2008 la Directive 2008/52/CE portant sur la médiation en matière civile et commerciale. Le postulat de départ de ce texte est qu’un « cadre juridique prévisible peut permettre aux citoyens de l’Union européenne (UE) de bénéficier pleinement des avantages de la médiation en tant que mécanisme de résolution des conflits, notamment sur le plan de la rentabilité et de la rapidité ». Puis, la médiation conventionnelle a été encadrée au sein du code de procédure civile. L’intégration de la Directive 2008/52/CE au sein du corpus de normes du droit interne positif a permis de créer une définition légale de la médiation en ces termes : « La médiation régie par le présent chapitre s'entend de tout processus structuré, quelle qu'en soit la dénomination, par lequel deux ou plusieurs parties tentent de parvenir à un accord en vue de la résolution amiable de leurs différends, avec l'aide d'un tiers, le médiateur, choisi par elles ou désigné, avec leur accord, par le juge saisi du litige ».Or, le mouvement d’expansion de la médiation semble freiné par un jeu de résistances. Certaines de ces résistances concernent le processus et sont prévisibles. D’autres tiennent à des variables exogènes, résultats de questionnements sur la médiation, le médiateur, l’office du juge, la déjudiciarisation, la déjuridictionnalisation, et l’ordre public. L’étude pose que l’essor de la médiation est contrarié par une méconnaissance de la médiation, ainsi qu’en raison d’une méconnaissance des acteurs de la médiation.Le mouvement d’encouragement des pouvoirs publics à la tentative de médiation, pour prévenir ou traiter des contentieux du droit privé, semble se muer en une politique globale de l’amiable, recentrée sur la mission du juge de concilier les parties. Cette politique de l’amiable persiste à produire des normes tendant, notamment, à encadrer la médiation, à créer un statut pour le médiateur, dans l’optique d’acculturer les justiciables à ce mode amiable.L’objet de la présente thèse est d’analyser les résistances à l’essor de la médiation en droit privé et leurs conséquences sur son développement en France. Il s’agit de saisir ces résistances et leurs enjeux ; et de redonner force au processus de médiation, en offrant à ses prescripteurs un faisceau d’arguments intelligibles. Mediation is a communication technique involving an impartial, neutral and independent third party to help individuals find a way out of their conflict crisis. By nature, mediation is a pacifying conflict resolution tool, based on the accountability of the parties. Attractive for its flexibility, praised for its moderate cost, the legislator encouraged its expansion. While Article 21 of the Code of Civil Procedure entrusts the judge with the task of reconciling the parties, mediation is becoming one of the tools favoured by the public authorities to enable this mission to be carried out. Thus, Law No. 95-125 of February 8, 1995, relating to the organization of the courts and civil, criminal and administrative procedure, establishes judicial mediation. It marks the beginning of a legislative anchoring in favour of this process. This initial movement in favour of mediation has accelerated in France, at the initiative of the European Union, which adopted Directive 2008/52/EC on mediation in civil and commercial matters on May 21, 2008. The premise of this text is that "a predictable legal framework can allow citizens of the European Union (EU) to fully benefit from the advantages of mediation as a dispute resolution mechanism, particularly in terms of cost-effectiveness and speed". Then, conventional mediation was framed in the Code of Civil Procedure. The incorporation of Directive 2008/52/EC into the body of norms of positive domestic law has made it possible to create a legal definition of mediation in the following terms: "Mediation governed by this chapter means any structured process, whatever its name, by which two or more parties attempt to reach an agreement with a view to the amicable resolution of their disputes, with the help of a third party, the mediator, chosen by them or appointed, with their agreement, by the judge hearing the dispute". However, the movement towards the expansion of mediation seems to be slowed down by a game of resistance. Some of these resistances are process-related and predictable. Others relate to exogenous variables, the result of questions about mediation, the mediator, the judge's office, diversion, dejurisdictionalization, and public order. The study posits that the development of mediation is thwarted by a lack of knowledge of mediation, as well as because of a lack of knowledge of the actors involved in mediation. The movement to encourage the public authorities to attempt mediation, to prevent or deal with private law disputes, seems to be turning into a global policy of amicable litigation, refocused on the judge's mission to reconcile the parties. This amicable policy persists in producing standards tending, in particular, to regulate mediation, to create a status for the mediator, with a view to acculturating litigants to this amicable method. The purpose of this thesis is to analyze the resistance to the rise of mediation in private law and their consequences on its development in France. It is a question of grasping these resistances and their stakes; and to give strength to the mediation process, by offering its prescribers a bundle of intelligible arguments.
Keywords: Amiable; Arbitrage (droit); Arbitration; Civil Law; Contract Law; Contrats; Droit civil; Droit des contrats; Droit privé; France; Mediation; Médiation; Private Law; Procedure Law; Procédure civile; Settlment

Social justice at the Commission for Conciliation Mediation and Arbitration (CCMA) and the critical role of the commissioner - Letlonkane, Katlego (Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study provides exploratory insight into the social justice mandate of the Commission for Conciliation Mediation and Arbitration (“CCMA”) in the context of labour relations in South Africa. As a vehicle for the advancement of social justice through the efficient resolution of labour disputes, the CCMA is a compelling actor in the pursuit of social justice in South Africa’s labour environment. Social justice as a legislative and policy imperative requires an investment in understanding its conceptual ideals and demands in order to empower those acting in its pursuit with the knowledge they need to fulfil its demands. The CCMA’s most critical functionary, its commissioner, holds the key to unlocking labour justice for many members of the public. One wonders, given the criticality of advancing social justice in labour relations, whether social justice is appropriately understood in order to enable the kind of decision-making that efficiently and consistently addresses the workings of power and inequality as they manifest in employment relationships. This study’s main provocation is to transform the pursuit of social justice (in the South African labour context, at least) from an elusive endeavour to a more tangible, realistic one. It attempts to offer a way of thinking about and applying social justice in the practice of labour dispute resolution in South Africa and the CCMA context. It critically explores the interwoven mechanisms of power, prejudice, and injustice and how these mechanisms work to sustain unequal labour relations. The commissioner’s role is thus a critical one, that involves a deliberate pursuit to recognise, understand and interrupt these movements of power and mitigate the effect of inequality. Any movement towards social justice that does not pay close attention to this matrix of power and prejudice threatens to dilute the transformative potency of social justice. This study identifies and discusses the decisions of commissioners that fall short of the kind of conscientious decision-making required by a mandate of social justice. Discussions in this study also point out significant achievements in centralising social justice principles in decision-making processes at the CCMA, where arbitrators, in reducing injustice and advancing justice in labour relations, show a conscientious consideration and appreciation of historical contexts, power, privilege and disadvantage. Living up to the constitutional imperative to transform society in the way of equality, commissioners ought to develop their agency and be empowered by the Constitution of the Republic of South Africa, 1996, to disrupt inequality. This study contributes to the understanding and clarification of social justice and its implications for the South African labour environment. It also posits ubuntu as an important consideration in the balancing exercise required to achieve justice.
Keywords: Arbitration; CCMA; Commission for Conciliation, Mediation, and Arbitration; Dispute resolution (Law); Mediation; Mediation and conciliation, Industrial; Officials and employees; Social justice